Overview of Systems Biology and Omics Technologies - Karahalil, Bensu (Current Medicinal Chemistry, 2016)
Traditional technologies using reductionist approach are relatively insufficient to solve problems in a biological system. Rather than a reductionist approach, systems biology uses a holistic and integrative approach to better figure out the whole process. Both qualitatively and quantitatively of biological system provide information about diseases, toxicities, therapies etc. Omics technologies, which systems biology brings, are valuable tools for comprehensive analyses. Automated DNA sequencers enabled the sequencing of genomes; microarray and mass spectrometry analysis permit global transcriptional profiling and lead to large-scale proteomic and metabolomics analysis. These high-throughput data need to be interpreted by bioinformatics. So far there has been no concrete published paper that compiles omics technologies according to PubMed database. In the present review, it was aimed to give brief description of systems biology and information on the advantages and disadvantages of omics technologies.
Keywords: proteomics